Realisasi pemberian ganti rugi asuransi keluarga berencana atas kecelakaan diri akibat pemakaian metode kontrasepsi efektif terpilih (MKET) = The Realization of Claims to Compensationby Family Planning ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
In an effort to improve family welfare through birth control by using more reliable contraseptive methods, there is a great need for legal protection which is directly concerned with the medical aspect to contraseption. One of the forms of this protection for Family Planning participants is Family Planning Insurance endorsed by a Memorandum of Agreement between the National Family Planning Coordination Agency (BKKBN) and jasa Raharja Accident Insurance Ltd. No. P/03/SP.P/V dated May 23 rd 1991. 088/H1C-104/F.3/91 In conformity with its objective, the Family Planning Insurance should be able to improve the quality and increase the degree of independence of the Family Planning participants in adopting the Chosen Effective Methods of Contraception paleT), i.e., IUD/ Spiral, Implant, Medical Operation on Women (MOW)/Tubectomy, and Medical Operation on Men (MOP)/Vasectomy. In the implementation of its objective, therefore, the Family Planning_Insurance puts an emphasis on protecting all participants of Family Planning (KB) and users of MKET by enhancing the concern and role of the general public, an intensive coordination as well as strong strategic support. In our existing legislation, there are still no regulations that are specifically concerned with matters pertaining to Family Planning Insurance. The purpose of this research, therefore, is to find out to what extent the Family Planning Insurance can provide. protection for the Family Planning participants who are continually faced with the risks of accidental injuries caused by the use of MKET, and how it develops in society. This research is an attempt to describe in a systematic, factual, and accurate way particular facts and problems related to the Family Planning Insurance and how claims for compensation are put into effect. The data were obtained by undertaking a field study, i.e., guided open interviews and questionnaires, which produced the primary data to support the secundary data. the he basis of the research objective and the adopted method, the findings indicate that a Family Planning Insurance is someone who voluntarily choses to use one of the contraseptive methods (MKET) and insures against any possible risks resulting from the use of a particular contraceptive to Jasa Raharja Accident Insurance Company Ltd. Out of 3698, there were no cases of deaths or permanent injuries, while 41 cases of complications and failures received claims for compensation in accordance with the guidelines of the Family Planning Insurance. In spite of that participation in Family Planning Insurance is voluntary in nature and the programme has not achieved the desired target so far, its concern for a fundamental issue in society and its goal of safeguarding public interest indicate that its development has the prospects of becoming an insurance with obligatory membership for fertile couples (PUS) who use KB-MKET.